Cuspal Displacement Induced by Bulk Fill Resin Composite Polymerization: Biomechanical Evaluation Using Fiber Bragg Grating Sensors. (12th April 2016) - Vinagre, Alexandra; Ramos, João; Alves, Sofia; Messias, Ana; Alberto, Nélia; Nogueira, Rogério
Abstract : Polymerization shrinkage is a major concern to the clinical success of direct composite resin restorations. The aim of this study was to compare the effect of polymerization shrinkage strain of two resin composites on cuspal movement based on the use of fiber Bragg grating (FBG) sensors. Twenty standardized Class II cavities prepared in upper third molars were allocated into two groups (n = 10 ). Restorations involved the bulk fill placement of conventional microhybrid resin composite (EsthetX® HD, Dentsply DeTrey) (Group 1) or flowable "low-shrinkage" resin composite (SDR ™, Dentsply DeTrey) (Group 2). Two FBG sensors were used per restoration for real-time measurement of cuspal linear deformation and temperature variation. Group comparisons were determined using ANCOVA( α = 0.05 ) considering temperature as the covariate. A statistically significant correlation between cuspal deflection, time, and material was observed (p < 0.01 ). Cuspal deflection reached 8.8  μ m (0.23% ) and 7.8  μ m (0.20% ) in Groups 1 and 2, respectively. When used with bulk fill technique, flowable resin composite SDR ™ induced significantly less cuspal deflection than the conventional resin composite EsthetX® HD (p = 0.015 ) and presented a smoother curve slope during the polymerization. FBG sensors appear to be a valid tool for accurate real-time monitoring of cuspal deformation.